Endophytic Fungi Isolated from Pteridium acquilinium and Newbouldia laevis Leaves Exhibited Antioxidant Activities and Inhibitory Potential Against Selected Clinical Bacteria Isolates - Ajah, Obinna; Unegbu, Chika Cecilia; Uzohuo, Emmanuel N; Anyanwu, Ogechi Ozioma; Okezie, Ugochukwu Moses; Anyanwu, Chioma; Joseph, Rich (Biology, Medicine, & Natural Product Chemistry, 2023)
Endophytic fungi are important components of plant micro-ecosystems and they exist usually inside the healthy tissues of living plants. Endophytes possess encouraging source of biologically active metabolites for pharmaceutical applications. This study isolated endophytic fungi from Pteridium acquilinium and Newbouldia laevis leaves and evaluated their antioxidant and antibacterial activities. A total of ten endophytic fungal species were isolated from the leaves of the plants, from which six were selected and identified, including; Epicoccum thailandicum; Trichoderma atroviride; Lasiodiplodia parva; Trichoderma yunnanense; Colletotrichum cobbittiense; and, Trichoderma crissum. Among the isolated fungi, Trichoderma crissum (266.2956 ± 84.84 µg/ml) and Lasiodiplodia parva (293.0755 ± 64.95 µg/ml) showed significant scavenging activity on comparison with ascorbic acid. Furthermore, the isolated endophytes showed potential antibacterial activity against the tested clinical pathogens. This study validates that endophytic fungi dwelling in the inner tissue of medicinal plants studied could be a potential source of biologically active metabolites with free radical scavenging activities and also for treatment of infectious diseases caused by Staphylococcus aureus, Pseudomonas aeroginosa and Escherichia coli.